2017
DOI: 10.1002/btpr.2559
|View full text |Cite
|
Sign up to set email alerts
|

Efficient secretion of three fungal laccases from Saccharomyces cerevisiae and their potential for decolorization of textile industry effluent—A comparative study

Abstract: Laccases are enzymes with a broad range of biotechnological applications and have, for example, the ability to oxidize many xenobiotics including synthetic dyes. In order to obtain an efficient laccase for the decolorization of dyes which spoil wastewater from the textile industry, genes encoding three various laccase enzymes were expressed in Saccharomyces cerevisiae. The expression of laccases from ascomycete Myceliophthora thermophila (MtL), and two basidiomycetes Trametes versicolor (TvL) and Trametes trog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Synthetic dyes in wastewater discharged by textile industry becomes one of the pollution issues in several decades (Antošová et. al., 2018;Kant, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic dyes in wastewater discharged by textile industry becomes one of the pollution issues in several decades (Antošová et. al., 2018;Kant, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the generalizability of our approach, we grew functionalised BC with two other enzymes: alpha-galactosidase enzyme Mel1 (a native S. cerevisiae secreted protein) and laccase enzymes from either Myceliophthora thermophila (MtLcc1) and Coriolopsis troggi (CtLcc1) 36 . All were cloned with a C-terminal CBD and either their native secretion signal peptide or the S. cerevisiae MFα signal peptide at the N-terminus (Supplementary Fig.…”
Section: Engineering Bc Materials Functionalisationmentioning
confidence: 99%
“…The yeast strain Saccharomyces cerevisiae BW31a transformed with expression plasmid pVT-100U-MtL [T2 mutant of MtL; MtL gene was mutated by directed evolution to enhance its expression in S. cerevisiae, Bulter et al (2003)] or pVT-100U-TtL (LCC1 isoform of TtL; TtL gene was synthetized with optimized codons for S. cerevisiae) was used for recombinant production of secreted laccases MtL and TtL from Myceliophthora thermophila and Trametes trogii, respectively (Antosova et al 2018). The yeast cells were cultivated in 500 mL (in a 2 L shake flask) of minimal YNB medium (6.7 g/L) without amino acids (ForMedium™) supplemented with 2% (w/v) glucose, 0.8% (w/v) alanine, 0.6 mM CuSO 4 and BSM-Ura (Brent supplement mixture drop-out uracil, ForMedium™) at the recommended concentration according to the provider's manual, at 30 °C for 3 days.…”
Section: Microorganisms and Cultivation Conditionsmentioning
confidence: 99%
“…Our results suggest that decolorization efficiency can be affected not only by the type of laccase, but also by the type of mediator, pH value, reaction temperature, and presence of other inhibitors in the reaction. The decolorization of industrial WWs by different laccase systems has been studied by Antosova et al (2018);Bello-Gil et al (2018) and Sondhi et al (2018); these studies have reported decolorization with up to 90% efficiency.…”
Section: Efficiencies Of Ww Decolorization and Detoxification Differ Among Laccases And Depend On Wastewater Propertiesmentioning
confidence: 99%